5′ isomiR variation is of functional and evolutionary importance. Issue 14 (23rd July 2014) - Tan, Geok Chin; Chan, Elcie; Molnar, Attila; Sarkar, Rupa; Alexieva, Diana; Isa, Ihsan Mad; Robinson, Sophie; Zhang, Shuchen; Ellis, Peter; Langford, Cordelia F.; Guillot, Pascale V.; Chandrashekran, Anil; et al.
Abstract: We have sequenced miRNA libraries from human embryonic, neural and foetal mesenchymal stem cells. We report that the majority of miRNA genes encode mature isomers that vary in size by one or more bases at the 3′ and/or 5′ end of the miRNA. Northern blotting for individual miRNAs showed that the proportions of isomiRs expressed by a single miRNA gene often differ between cell and tissue types. IsomiRs were readily co-immunoprecipitated with Argonaute proteins in vivo and were active in luciferase assays, indicating that they are functional. Bioinformatics analysis predicts substantial differences in targeting between miRNAs with minor 5′ differences and in support of this we report that a 5′ isomiR-9–1 gained the ability to inhibit the expression of DNMT3B and NCAM2 but lost the ability to inhibit CDH1 in vitro . This result was confirmed by the use of isomiR-specific sponges. Our analysis of the miRGator database indicates that a small percentage of human miRNA genes express isomiRs as the dominant transcript in certain cell types and analysis of miRBase shows that 5′ isomiRs have replaced canonical miRNAs many times during evolution. This strongly indicates that isomiRs are of functional importance and have contributed to the evolution of miRNA genes.